2022
DOI: 10.26832/24566632.2022.070305
|View full text |Cite
|
Sign up to set email alerts
|

Screening of some sweet potato (Ipomoea batatas (L.) Lam) genotypes for yield and damage by Cylas puncticollis under rainfed conditions in Umudike, Southeastern Nigeria

Abstract: A field experiment was conducted at the National Root Crops Research Institute, Umudike, Southeastern Nigeria during the 2015 and 2016 cropping seasons to evaluate diversity among F1 population of sweet potato, namely: Sauti × 442162 (6), Ligri × Faara (17), Sauti × Bohye (17), including two checks (Umuspo 3 and TIS 87/0087). This experiment was laid out in a randomized complete block design with three replicates under rainfed condition. Data on fresh storage root yield were recorded at 120 days after planting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…For sweetpotato, there can be superior parental genotypes identified that favor general combining ability, but there are also specific combining abilities which can be identified when tracking a particular trait (such as SPW resistance) for crop improvement (Mugisa et al 2022). While historical trends have led some to regard SPW resistance as less likely to be achieved in SSA, some recent efforts have shown promise (Kagimbo et al 2020;Joseph et al 2022;Mugisa et al 2022). In at least one of these recent SSA efforts (Kagimbo et al 2020), there is indication that the germplasm resistance may be based on a mechanism in common with that found from selection efforts that were successful in the USA.…”
Section: Host Plant Resistancementioning
confidence: 99%
“…For sweetpotato, there can be superior parental genotypes identified that favor general combining ability, but there are also specific combining abilities which can be identified when tracking a particular trait (such as SPW resistance) for crop improvement (Mugisa et al 2022). While historical trends have led some to regard SPW resistance as less likely to be achieved in SSA, some recent efforts have shown promise (Kagimbo et al 2020;Joseph et al 2022;Mugisa et al 2022). In at least one of these recent SSA efforts (Kagimbo et al 2020), there is indication that the germplasm resistance may be based on a mechanism in common with that found from selection efforts that were successful in the USA.…”
Section: Host Plant Resistancementioning
confidence: 99%